Fracture Mechanism Change at a Heterogeneous Polymer-Polymer Interface Reinforced with in Situ Graft Copolymers - Kim, Hoyeon (Langmuir : the ACS journal of surfaces and colloids, 2018)
Dynamic secondary-ion mass spectroscopy (DSIMS) was used to investigate the change in the failure mechanism at a heterogeneous polymer-polymer interface (polystyrene (PS)/polyamide (nylon 6, Ny6)) reinforced with in situ graft copolymers produced by the reaction between Ny6 molecules and poly(styrene- co-maleic anhydride) at the interface. The variation in fracture toughness with bonding time and temperature has been explained by two different failure mechanisms: adhesive failure at the interface for short bonding times and when the bonding temperature is low and cohesive failure between chains at the interface and bulk PS for longer bonding times and when the bonding temperature is high. DSIMS results provide the direct experimental evidence that the nonreactive molecules (PS) diffuse away from the high-potential interface, which induces the cohesive failure in the bulk of the nonreactive molecules (PS) after long annealing times. The change in the adhesion strength with temperature could also cause a change in the failure mechanism. Common features of the fracture mechanisms at heterogeneous interfaces reinforced by the in situ graft copolymers are outlined, which are independent of the polymer crystallinity